2023
DOI: 10.1002/lary.30683
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Sphenoid Sinus Fungus Ball: A Nine‐year Retrospective Study of 77 Cases

Abstract: ObjectiveThis study aimed to investigate the clinical characteristics of sphenoid sinus fungus ball (SSFB) to help increase the accuracy of diagnosis and efficiency of treatment.MethodsWe retrospectively analyzed the data of 77 patients who were histopathologically diagnosed with SSFB.ResultsThe mean age of SSFB patients was 52.4 years (range 25–84), and 47 patients (61.0%) were female. Compared to age‐matched and sex‐matched chronic rhinosinusitis (CRS) patients, headache was more common in SSFB patients (79.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
(126 reference statements)
0
2
0
Order By: Relevance
“…Fungal balls are more common in females than in males and in those in their fifties [6,21,22]. Although a consensus on the explanation for this phenomenon is lacking, the longer life expectancy and the effect of menopause in females have been proposed as possible causes [21,23]. Our previous study observed that the femaleto-male ratio was highest at 51-60 years of age (2.02).…”
Section: Discussionmentioning
confidence: 92%
“…Fungal balls are more common in females than in males and in those in their fifties [6,21,22]. Although a consensus on the explanation for this phenomenon is lacking, the longer life expectancy and the effect of menopause in females have been proposed as possible causes [21,23]. Our previous study observed that the femaleto-male ratio was highest at 51-60 years of age (2.02).…”
Section: Discussionmentioning
confidence: 92%
“…They also reported that plasma glucose level, HbA1C, and duration of diabetes were insignificantly predictors for fungal sinusitis. Moreover, Jiang et al [14] demonstrated sinus fungus patients had a higher prevalence of diabetes.…”
Section: Fig (1): Vitamin D Of the Studied Patientsmentioning
confidence: 99%